2011
DOI: 10.1099/jmm.0.028357-0
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal DNA is not detectable in the blood of healthy carrier children by real-time PCR targeting the lytA gene

Abstract: The diagnosis of invasive pneumococcal disease (IPD) is currently based on culture methods, which lack sensitivity, especially after antibiotic therapy. Molecular methods have improved sensitivity and do not require viable bacteria; however, their use is complicated by reports of low specificity with some assays. The present study investigated the specificity of a real-time PCR targeting lytA for the detection of IPD. A group of 147 healthy children, aged 6 months to 16 years (mean 6.4 years, median 4.9 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
0
24
3
Order By: Relevance
“…Controls in those studies were not a random selection from the community but were attending hospital for allergies or celiac disease [4] or had previously been vaccinated with PCV-9 in a clinical trial [10], were older (mean age of approximately 5 years), had lower prevalence (50%) [4, 10] and density [4] of nasopharyngeal pneumococcal carriage, and possibly had higher socioeconomic status. The South African study also used serum rather than whole blood [10].…”
Section: Discussionmentioning
confidence: 99%
“…Controls in those studies were not a random selection from the community but were attending hospital for allergies or celiac disease [4] or had previously been vaccinated with PCV-9 in a clinical trial [10], were older (mean age of approximately 5 years), had lower prevalence (50%) [4, 10] and density [4] of nasopharyngeal pneumococcal carriage, and possibly had higher socioeconomic status. The South African study also used serum rather than whole blood [10].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative PCR has been useful for detection of pneumococcal DNA in blood specimens, especially from children (Azzari et al, 2011;Marchese et al, 2011), but detection in respiratory specimens has been difficult to interpret because of the inability to differentiate colonization from infection (Dagan et al, 1998;Murdoch et al, 2003). The choice of PCR assay can have a noticeable A. M. Werno, T. P. Anderson and D. R. Murdoch effect on results.…”
mentioning
confidence: 99%
“…Real-time PCR on whole blood allowed identification of additional possible Sp cases: in young children, culture and PCR together detected 8 times more cases than culture alone. Recent data from the PERCH study suggest that lytA PCR may have limited specificity (personal communication, MD Knoll): in several PERCH sites, DNA-emia was seen in healthy controls, which could be explained by the transfer of genetic material from the nasopharynx to the blood in colonized children; however, these results run counter to earlier analyses showing high specificity for blood PCR [39,40]. Elsewhere, we reported findings from latent class analysis models combining laboratory and radiological data from our patients (Blake et al, accepted for publication): we showed that standardized CXR interpretation was the best approach to diagnosing Sp pneumonia and estimated that one third of pneumonia cases were attributable to pneumococcus, a proportion that increased with age from 20 to 50% and was consistent with clinical trials and observational data [5].…”
Section: Discussionmentioning
confidence: 87%